Status of Black-necked Cranes in Arunachal Pradesh - Singh, D. N. (Indian Forester, 2000)
The Black-necked Cranes arrive in Arunachal Pradesh during winter months to keep away from cold climate of Tibet. They have been reported in the past from Gandhi gram and Apatani plateau areas of the State but at present they are restricted to Santhi valley and Zemithang areas only. The present paper is a study on its range, status and behaviour in Arunachal Pradesh.